2012
DOI: 10.1152/jn.00993.2011
|View full text |Cite
|
Sign up to set email alerts
|

Domain III regulates N-type (CaV2.2) calcium channel closing kinetics

Abstract: Yarotskyy V, Gao G, Peterson BZ, Elmslie KS. Domain III regulates N-type (Ca V 2.2) calcium channel closing kinetics. J Neurophysiol 107: 1942-1951, 2012. First published December 28, 2011 doi:10.1152 doi:10. /jn.00993.2011 and Ca V 1.2 (L-type) calcium channels gate differently in response to membrane depolarization, which is critical to the unique physiological functions mediated by these channels. We wondered if the source for these differences could be identified. As a first step, we examined the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The pipette solution contained 104 mM NMG·Cl, 14 mM creatine·PO 4 , 6 mM MgCl 2 , 10 mM NMG·Hepes, 5 mM Tris·ATP, 10 mM NMG 2 ·EGTA, and 0.3 Tris 2 ·GTP, with pH 7.4 and an osmolarity of 300 mOsm. Ionic currents were recorded and analyzed as previously described (19,58). Recordings were carried out at room temperature, and the holding potential was −80 mV.…”
Section: Methodsmentioning
confidence: 99%
“…The pipette solution contained 104 mM NMG·Cl, 14 mM creatine·PO 4 , 6 mM MgCl 2 , 10 mM NMG·Hepes, 5 mM Tris·ATP, 10 mM NMG 2 ·EGTA, and 0.3 Tris 2 ·GTP, with pH 7.4 and an osmolarity of 300 mOsm. Ionic currents were recorded and analyzed as previously described (19,58). Recordings were carried out at room temperature, and the holding potential was −80 mV.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted here, that the Cdk5 inhibitor roscovitine (Ro) has also shown to affect Ca V 3.1 channel activity. Specifically, the drug seems to inhibit these channels in part by stabilizing the closed-inactivated state [ 27 ]. In addition, it has been reported that Ro affects Ca V 2.2 (N-type) current kinetics [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…If prior use of ( R )-roscovitine by experimentalists is any indication, these novel analogs with greater potency and efficacy should be valuable tool compounds. Such tool use has previously aided the study of Cav2 single channel conductance (Weber et al, 2010), Cav2 VGCC structure and function (Yarotskyy et al, 2012), Cav2 VGCC permeation (Buraei et al, 2014), the calcium ion control of transmitter release from synapses (Wen et al, 2013; Satake and Imota, 2014), and calcium ion dynamics in non-neuronal cells (Tamma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%